The virgin terrorist. (Economist, 2018)
The article reports on the vehicle-ramming attack that occurred on April 23, 2018 in Toronto, Ontario, perpetrated by computer programmer Alek Minassian. Topics discussed include Minassian's proclamation of an Incel Rebellion on the social networking site Facebook, his plan to murder women because they would not have sex with him, and the 1989 case of woman-hating killer Marc Lépine.